PERAN DAN RAGAM JENIS BAHAN AJAR (CETAK DAN NON CETAK) YANG RELEVAN DALAM PEMBELAJARAN BAHASA DAN SENI BUDAYA DI SDI SURYA BUANA MALANG - Dwi Hasanah, Kartini; Dewi Anita Silvina Wahab; Jazilatun Nawali; Helda Ivtari Savika; Mohammad Zubad Nurul Yaqin (Universitas Islam Raden Rahmat Malang, 2024)
Abstrack This research will explore information about the importance of the role and various types of teaching materials (printed and non-printed) that are relevant in learning language and arts and culture at the basic education level, especially at the elementary school level, namely at SDI Surya Buana Malang. The research method used is qualitative research and literature study. Data was obtained through in-depth interviews with teachers, classroom observations, documentation, academic journals, books, articles and relevant research reports. The findings from the research show that there are various types of printed and non-printed teaching materials, supporting factors and challenges that influence the implementation of printed and non-printed teaching materials, the positive impact of the implementation of printed and non-printed teaching materials, and the implementation of teaching materials that are integrated between printed and non-printed. print language and arts and culture learning in Class 2 of SDI Surya Buana Malang. The aim of this research is to provide scientific treasures and an in-depth understanding of the role and various types of teaching materials (print and non-print) that are relevant in language and arts and culture learning at SDI Surya Buana Malang. In conclusion, the role of printed and non-printed teaching materials is very important to implement in the learning of Indonesian language and arts and culture at primary level schools, so that they are appropriate and achieve learning objectives. Therefore, it is recommended that all levels understand the role and implement printed and non-printed teaching materials in the learning process. Keywords: Variety, Role, Teaching Materials Abstrak Penelitian ini akan mengeksplor informasi tentang pentingnya peran dan ragam jenis bahan ajar (cetak dan non cetak) yang relevan dalam pembelajaran bahasa dan seni budaya dalam tingkat pendidikan dasar, khususnya di tingkat sekolah dasar yaitu di SDI Surya Buana Malang. Metode penelitian yang digunakan adalah penelitian kualitatif dan studi literatur. Data diperoleh melalui wawancara mendalam dengan guru, observasi kelas, dokumentasi, jurnal akademik, buku, artikel, dan laporan penelitian yang relevan. Hasil temuan dari penelitian menunjukkan bahwa ragam jenis bahan ajar cetak dan non cetak, factor pendukung dan tantangan yang mempengaruhi implementasi bahan ajar cetak dan non cetak, dampak positif dari implementasi bahan ajar cetak dan non cetak, dan Implementasi bahan ajar yang diintegrasikan antara cetak dan non cetak pembelajaran Bahasa dan seni budaya di Kelas 2 SDI Surya Buana Malang. Tujuan dari penelitian ini memberikan khazanah keilmuan dan pemahaman yang mendalam tentang peran dan ragam jenis bahan ajar (cetak dan non cetak) yang relevan dalam pembelajaran bahasa dan seni budaya di SDI Surya Buana Malang. Kesimpulannya, bahwa peran bahan ajar cetak dan non cetak ini sangat penting diimplementasikan pada pembelajaran bahasa Indonesia dan Seni Budaya disekolah tingkat dasar, agar sesuai dan tercapai tujuan pembelajaran. Oleh karena itu, disarankan agar semua tingkat memahami peran dan menimpelemntasikan bahan ajar cetak dan non cetak pada proses pembelajaran. Kata kunci: Ragam, Peran, Bahan Ajar